(untitled) (Journal of Naval Architecture and Marine Engineering, 2009)
The objective of this work is to study heat and mass transfer in an unsteady MHD free convective flow past an infinite vertical plate with constant suction numerically.Â Dimensionless governing equations of the problem have been solved by using finite difference technique. Numerical solutions for temperature, velocity, concentration have been obtained for suitable parameters like Grashoff number, mass Grashoff number, Prandtl number and Schmidt number. Rate of heat transfer and mass transfer are studied. The results obtained are discussed with the help of graphs and tables to observe effect of various parameters concerned in the problem under investigation. Stability and convergence of the finite difference scheme is established. Key words: MHD, unsteady, constant suction, finite difference technique, Heat and mass transfer. doi:10.3329/jname.v5i1.1785 Journal of Naval Architecture and Marine Engineering Vol. 5, No.Â 1 (June, 2008) 27-36